Low-intensity aerobic training reduces macrophages infiltration and improves morphological characteristics of soleus skeletal muscle from mdx mice (Revista Brasileira Multidisciplinar, 2024)
Duchenne Muscular Dystrophy (DMD) is characterized by the absence of the dystrophin protein. The absence of this protein determines recurrent injuries in muscle tissue progressing to necrosis and generalized weakness, leading to the patient’s death due to respiratory and/or cardiac failure. There is no cure for DMD. However, some exercise programs could minimize the disease's progression. Low-intensity training has been used as a rehabilitation program for dystrophic muscles, although the effects are still unclear. This study aimed to analyze the effects of low-intensity aerobic training on the general morphological aspects of the skeletal muscle of mdx mice.  Eighteen male mice were divided into three groups with six animals each: (mdx sedentary, mdx trained, and wild-type sedentary). The low-intensity training was performed on a treadmill running during the 37 sessions. After the experiments, the animals were euthanized, and the soleus muscle was excised for histological and immunofluorescence analyses. The training (37 sessions) showed an improvement intoning the morphological aspects of soleus mdx mice and a reduction of macrophage infiltration. The low-intensity training can minimize the inflammatory process and reverse morphological alteration in the soleus muscle of the mdx mice.